Giant Halo in 66Ca Within Relativistic Continuum Hartree–Bogoliubov Theory Combined with Lipkin–Nogami Method - Chang Zhou; Peng Guo; Xiaofei Jiang (Particles)
The impact of the Lipkin–Nogami (LN) method on a giant halo is investigated within the relativistic continuum Hartree–Bogoliubov (RCHB) theory. The ground-state properties of Ca isotopes obtained from RCHB and RCHB+LN calculations are presented. The results show that the LN correction does not change the range of Ca isotopes with a giant halo. Taking 66Ca as an example, the neutron density distribution with LN correction is found to be slightly more diffused, which can be illustrated by the enlargement of the root mean square radius and the enhancement of the relative contribution in neutron <semantics>3s1/2</semantics> level.